Investigation of Ginsenosides and Antioxidant Activities in the Roots, Leaves, and Stems of Hydroponic-Cultured Ginseng (Panax ginseng Meyer) - Song, Yu-Na (Prev Nutr Food Sci, 2019)
There has been very little reported on ginsenoside composition and antioxidant activity of hydroponic-cultured ginseng roots (HCR), leaves (HCL), and stems (HCS). We profiled 6 ginsenoside compounds in HCR, HCL, and HCS using high-performance liquid chromatography. Antioxidative activity of HCR, HCL, and HCS were evaluated using total phenolic content (TPC) and total flavonoid content (TFC), 2,2-diphenyl-1-picrylhydrazyl (DPPH) free-radical-scavenging activity assays, and ferric reducing antioxidant power (FRAP) assays. Total ginsenoside contents of HCL and HCS were significantly higher than that of HCR (P<0.05). Rb1 was detected in HCR (23.02 mg/g) but was detected at very low levels in HCL and HCS (2.07~7.30 mg/g). Rg1 was the most abundant ingredient in HCL, followed by Rd; this was different than for HCR and HCS. The TPC and TFC ranged from 52.82~155.31 mg gallic acid equivalent/100 g and 194.71~256.52 mg quercetin equivalent/100 g, respectively, of which HCL contained the highest levels. Moreover, HCL was the most effective in both DPPH and FRAP activities. In this study, we also evaluated the inhibitory effect of HCR, HCL, and HCS on the activities of mushroom tyrosinase through whitening activity test. The inhibitory effect of HCL on tyrosinase activity was higher than that of HCR and HCS. This study provides information about ginsenoside contents and the antioxidative activity of hydroponic-cultured ginseng, and suggests that the whole ginseng plant (including roots, leaves, and stems) may be a beneficial functional vegetables.